(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
It is necessary to regularly monitor the dynamics of physical development and physical fitness data of 9-11th grade students in order to determine the optimal loads, increase the desire to engage in physical exercises, choose the most reasonable exercises and make effective adjustments to training plans in time